1991
DOI: 10.1177/00220345910700070501
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characterization of Staphylococcus aureus from the Tongues of Children

Abstract: Three hundred and seven children who had no diseases other than dental disease were examined for their oral carriage of Staphylococcus aureus, the most common persistent human pathogen. Eighty-four percent of them were positive for staphylococci, and 33% were positive for S. aureus. Among the 100 strains of S. aureus isolated, 40 strains produced enterotoxin, and 19 strains produced exfoliative toxin. Their susceptibility to antibiotics was also investigated: Six strains demonstrated resistance to methicillin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 13 publications
2
43
1
3
Order By: Relevance
“…5 Of concern was the small but significant number of MRSA isolates recovered from oral specimens. This may reflect the increasing reservoir of community MRSA, for example, 17% of nursing homes in one locality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Of concern was the small but significant number of MRSA isolates recovered from oral specimens. This may reflect the increasing reservoir of community MRSA, for example, 17% of nursing homes in one locality.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some oral infections are caused at least in part by S. aureus, for example, angular cheilitis, 2 parotitis 3 and staphylococcal mucositis. 4 Furthermore there is now a growing body of evidence to suggest that staphylococci can be frequently isolated from the oral cavity of particular patient groups such as children, 5 the elderly 4 and some groups with systemic disease, such as the terminally ill, 6 rheumatoid arthritis 7 and patients with haematological malignancies. 8 The aim of this study was to identify the rate of S. aureus isolation from specimens submitted to a regional diagnostic oral microbiology laboratory over the period 1998-2000.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have described the oral carriage of meticillin-resistant S. aureus (MRSA) (30,39). In addition, Miyake et al (22) found that 19% of the S.aureus isolates from oral samples produced exfoliative toxin and 40% of them enterotoxins.…”
Section: Figurementioning
confidence: 99%
“…Following work by Gordon et al (1966), studies have been conducted to analyse bacteria in the tongue biofilm, but most have targeted a limited number of bacterial species (Frisken et al, 1990;Miyake et al, 1991;van Winkelhoff et al, 1986). Comprehensive analyses of tongue biofilm microflora using culture methods or molecular biological methods have recently been reported (Hartley et al, 1996(Hartley et al, , 1999Kazor et al, 2003;Milnes et al, 1993).…”
Section: Introductionmentioning
confidence: 99%